Ensembl 2018. Issue Volume 46:Issue D1(2018) (16th November 2017) - Zerbino, Daniel R; Achuthan, Premanand; Akanni, Wasiu; Amode, M Ridwan; Barrell, Daniel; Bhai, Jyothish; Billis, Konstantinos; Cummins, Carla; Gall, Astrid; Girón, Carlos García; Gil, Laurent; Gordon, Leo; et al.
Abstract: The Ensembl project has been aggregating, processing, integrating and redistributing genomic datasets since the initial releases of the draft human genome, with the aim of accelerating genomics research through rapid open distribution of public data. Large amounts of raw data are thus transformed into knowledge, which is made available via a multitude of channels, in particular our browser (http://www.ensembl.org ). Over time, we have expanded in multiple directions. First, our resources describe multiple fields of genomics, in particular gene annotation, comparative genomics, genetics and epigenomics. Second, we cover a growing number of genome assemblies; Ensembl Release 90 contains exactly 100. Third, our databases feed simultaneously into an array of services designed around different use cases, ranging from quick browsing to genome-wide bioinformatic analysis. We present here the latest developments of the Ensembl project, with a focus on managing an increasing number of assemblies, supporting efforts in genome interpretation and improving our browser.